Consumer behavior dynamics of Chinese minorities. Issue 1 (2014) - ,; ,; ,; ,
Abstract : Purpose – Meat consumption decisions within a religious context can differ significantly from purchase decisions where religion does not play a key role. The purpose of this study is to investigate the determinants of Halal meat consumption within a Chinese Muslim population using the "marketing theory of planned behavior". The role of self‐identity as a Muslim and dietary acculturation in the host culture is investigated.Design/methodology/approach – The study is based on a questionnaire survey. Cross‐sectional data were collected through a survey of 368 Muslim participants, mainly from Xinjiang province in China. Data were analyzed by a series of regression analyses to test the model and the moderating effects of self‐identity and dietary acculturation on behavioral intention.Findings – The results indicate that motivation to comply with religious requirements, and personal conviction, have a positive attitude toward behavioral intention to consume Halal meat. However, perceived control has a negative relationship with behavioral intention to eat Halal meat among Muslims. Results also show that in general, Halal meat consumption is determined by the pressure of others, personal conviction, and the perceived control.Practical implications – For marketing managers, Muslims with a low Muslim identity can be motivated to buy Halal meat by communicating through slogans that focus on the individual's opportunity to make his or her own choice(s).Originality/value – This paper will prove valuable to food‐policy decision makers and food marketers, who might pursue identity and/or acculturation‐related strategies in their distribution and communication efforts targeting the growing Halal food market segment in China and globally.